Evaluation of Vitamin D Deficiency in Patients with Chronic Liver Disease and Its Clinical Significance - Bal Kishan Gupta; Makkhan Lal Saini; Hardeva Ram Nehara; Shyam Lal Meena; Meghraj Saini; Jigyasa Gupta (International Journal of Nutrition, 2016)
Introduction: Vitamin D deficiency has been reported highly prevalent in Chronic liver disease (CLD) and there is an emerging interest to explore the relationship of vitamin D deficiency and severity of various types of CLD. Aim: To evaluate vitamin D level in patients with various type of CLD and clinical significance of its deficiency. Materials and Methods: Serum vitamin D levels were measured by ELFA in 100 patients (91 male and 9 female) suffering from CLD. The degree of liver dysfunction was estimated by Child Pugh criteria and Model for End stage Liver Disease (MELD) score. Results: Prevalence of vitamin D deficiency and insufficiency were 43% and 42% respectively among CLD patients. Low levels of vitamin D were associated with leucopenia or leucocytosis indicating increased risk of infection. On Linear regression vitamin D level showed significant negative correlation with Child Pugh score (r = – 0.7382, p<0.0001) and MELD score (r = – 0.6673, p<0.0001). Our study shows low vitamin D level was associated with poor outcome (mean vitamin D level 10.38 ± 2.35 who died vs 23.14 ± 6.68 who survived and discharged). Conclusion: CLD is associated with a significantly low level of vitamin D which was independent to patient’s gender, BMI, residence and education level. The lower level of vitamin D is associated with severity of CLD, mortality and increased risk for infections. Awareness of serum vitamin D level in patients with CLD is important to improve outcome.
Keywords: Vitamin D Deficiency